The distribution of share capital of Italian banking companies - E. RIENZI (PSL Quarterly Review, 2014)
The article provides analysis based on the results of a statistical enquiry ordered by the Italian Government to ascertain the distribution of the capital of Italian Limited Companies on December 31, 1945. The subject dealt with is therefore part of a broader enquiry in course of publication. This inquiry, new in Italy, throws valuable light on some controversial aspects of present-day capitalistic structure. Among other things, it ascertains in the case of Italy the degree of concentration of national and private capital, their reciprocal combinations, the connections existing between the several Companies, the extent to which foreign capital is interested in them.